The - Barr, Nicholas (Oxford University Press, 2001)
Barr contends that the welfare state exists for reasons besides poverty relief, reasons arising out of pervasive problems of imperfect information, risk and uncertainty. As a result, he argues, the welfare state is here to stay, since 21st century developments don't address these additional reasons